The Influence of Financial Structure, Financial Literacy and Financial Behavior on Household Financial Resilience Using Financial Inclusion and Financial Decision as Intervening Variables On Cancer Survivors Household In East Java During COVID-19 Pandemic - Maria Yovita R Pandin; Tri Ratnawati; Indrawati Yuhertiana (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
The research aims to analyze the influence of financial structure, financial literacy and financial behavior on household financial resilience where financial inclusion and financial decisions are intervening variables in families of cancer survivors in East Java during the Covid 19 pandemic. It uses a quantitative approach by collecting data through surveys. The population of this study is the overall data on the number of women with breast cancer in East Java. Based on secondary data obtained from the 2018 Indonesian Health Profile issued by the Ministry of Health of the Republic of Indonesia, there were 937 breast cancer sufferers in East Java up to 2018. The results showed of the determination coefficient test obtained the number 0.547826, which means that the variables used in the study are Financial Structure, Financial Literacy, Financial Behavior, Financial Inclusion and Financial Decisions can influence the Financial Resilience variable by 54.78%. Financial inclusion and financial decisions as intervening variables, where financial inclusion has a negative and significant effect, while financial decisions have a positive and significant effect.